The investigation of the level of self-directed learning readiness according to the locus of control and personality traits of preschool teacher candidates - (:unkn) unknown (International Electronic Journal of Elementary Education, 2016)
The aim of this study is to investigate the relationship between the level of self-directed learning readiness, locus of control and the personality traits of preschool teacher candidates. The survey method was used for this study. The study group consisted of 151 teacher candidates who volunteered to participate in the study from Preschool Education department at Atatürk Faculty of Education, Marmara University. A Demographic Form, Self-Directed Learning Readiness Scale, The Big Five Inventory and Locus of Control Scale were used as the data collection tools. The results of the study indicated that there is a significant relationship between the level of self-directed learning readiness, “extraversion” and “conscientiousness” traits of personality and “personal control” subscale of the locus of control. The results could be discussed in terms of training the preschool teacher candidates to improve their self-directed learning readiness levels by considering their personality traits and locus of control. © 2016, International Electronic Journal of Elementary Education. All rights reserved.
Keywords: Big five personality traits; Locus of control; Preschool teacher candidates; Self-directed learning